tS – ELEMENTS - Danilishyn, Illia; Danilishyn, Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2023)
We shall consider structure: A is expelled from B. A, B-are any, in particular, A may be action, action in the right direction and with the right goal (action with the so-called target weights [1]).